Design and Development of Information System of Population and Civil Registration Office of Malang Regency Based on Android - Farid Wahyudi; Listanto Tri Utomo (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
In the service in the population and civil registration services of Malang Regency, there are still many problems that are often faced by employees and the community. Among them is the lack of information about the requirements in taking care of population administration and civil records so that there are still many people who have to return to complete the required requirements or a long queue due to an error in writing the name, date of birth and so forth. The application developed in this research is based on Android. With the support of the development of the operating system on mobile, especially Android, problems faced by the community can be overcome. The people of Malang Regency are no longer confused about finding information about the requirements to take care of population administration at the Malang Regency Population and Civil Registry Office. DOI : https://doi.org/10.26905/jeemecs.v3i2.4345